Neuroimaging in cerebellar ataxia in childhood: A review. Issue 5 (24th June 2022) - Serrallach, Bettina L.; Orman, Gunes; Boltshauser, Eugen; Hackenberg, Annette; Desai, Nilesh K.; Kralik, Stephen F.; Huisman, Thierry A. G. M.
Abstract: Ataxia is one of the most common pediatric movement disorders and can be caused by a large number of congenital and acquired diseases affecting the cerebellum or the vestibular or sensory system. It is mainly characterized by gait abnormalities, dysmetria, intention tremor, dysdiadochokinesia, dysarthria, and nystagmus. In young children, ataxia may manifest as the inability or refusal to walk. The diagnostic approach begins with a careful clinical history including the temporal evolution of ataxia and the inquiry of additional symptoms, is followed by a meticulous physical examination, and, depending on the results, is complemented by laboratory assays, electroencephalography, nerve conduction velocity, lumbar puncture, toxicology screening, genetic testing, and neuroimaging. Neuroimaging plays a pivotal role in either providing the final diagnosis, narrowing the differential diagnosis, or planning targeted further workup. In this review, we will focus on the most common form of ataxia in childhood, cerebellar ataxia (CA). We will discuss and summarize the neuroimaging findings of either the most common or the most important causes of CA in childhood or present causes of pediatric CA with pathognomonic findings on MRI. The various pediatric CAs will be categorized and presented according to (a) the cause of ataxia (acquired/disruptive vs. inherited/genetic) and (b) the temporal evolution of symptoms (acute/subacute, chronic, progressive, nonprogressive, and recurrent). In addition, several illustrative cases with their key imaging findings will be presented.